Sex differences in subcortical aging: A nomogram study of age, sex, and apoe (N = 9, 414): Neuroimaging / imaging and genetics. (7th December 2020) - Ching, Christopher; Abaryan, Zvart; Santhalingam, Vigneshwaran; Zhu, Alyssa; Bright, Joanna; Jahanshad, Neda; Thompson, Paul M
Abstract: Background: Common variants in the APOE gene are associated with cognitive decline, brain atrophy and risk for developing Alzheimer's disease (AD). APOE polymorphism effects may also vary with age, sex, body mass index (BMI), and other risk factors. Here we create percentile charts ‐ or 'nomograms' ‐ plotting the trajectory of subcortical volumes with age, stratified by sex and by APOE genotype, in a large population‐based sample from the UK Biobank. We hypothesized that age effects would differ in men and women and APOE e4 allele carriers would tend to show steeper age‐related decline compared to those carrying APOE e3 and e2 genotypes. Method: T1‐weighted brain MRI UK Biobank data (N=9, 414; age range: 44‐79 yrs (Table 1) were processed using FreeSurfer v5.3 to derive quality inspected volumes averaged across hemispheres: lateral ventricles, hippocampus, thalamus, putamen, pallidum, amygdala, caudate, nucleus accumbens, and intracranial volume (ICV). The R package rstandard was used to adjust subcortical volumes for effects of ICV and BMI. R package GAMLSS, specifically the centile function, was used to compute percentile curves for each ROI based on standardized residuals, with ROI volume as the dependent variable and age as the independent variable. Separate models were fitted by sex and for each APOE genotype and visualized for trends with age. Result: Nomograms for the full cohort showed trends for increasing lateral ventricle and decreasing thalamus, putamen, hippocampus, amygdala, and nucleus accumbens volumes with increasing age (Figures 1‐2). In men, volumes decreased at a faster rate until age 60, when volumetric decline in women appeared to accelerate and catch up with males. Nomograms separated by APOE genotype (Figure 1) all followed similar patterns, though smaller samples of APOE e2/2 and e4/4 genotypes limit the interpretability of those age trends. Conclusion: Nomograms plotted by sex show a differential age trajectory for men and women offering clues for future sex‐dependent brain related assessment and intervention. APOE genotype did not strongly influence nomograms, though a greater number of APOE e2/2 and e4/4 individuals are needed to obtain reliable normative trends.